2011
DOI: 10.1177/1534734611418571
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Gentamicin Penetration in Lower Extremity Ischemic Tissues With Ulcers

Abstract: The aims of the study were to analyze the penetration of gentamicin in foot ulcers in patients with different severities of peripheral arterial disease (PAD) and to determine significant parameters affecting lower limb tissue concentrations. Patients undergoing debridement of a wound or an amputation procedure were included. All patients received a 120 mg or 240 mg intravenous dose of gentamicin prior to the procedure. Patients were classified according to the degree of PAD. Tissue and serum samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For example, Zammit et al [38] have investigated the impact of increasing severity of PAD on the tissue concentration of gentamicin in patients with ischemic ulcers. These authors have found a strong inverse correlation between PAD severity and local limb tissue concentration of the antibiotic drug, suggesting that local blood flow regulation is an important determinant of drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zammit et al [38] have investigated the impact of increasing severity of PAD on the tissue concentration of gentamicin in patients with ischemic ulcers. These authors have found a strong inverse correlation between PAD severity and local limb tissue concentration of the antibiotic drug, suggesting that local blood flow regulation is an important determinant of drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of gentamicin in skeletal muscle and subcutaneous tissue varies depending on gentamicin concentration in serum, gender, age, the degree of peripheral arterial disease and pathological state of the tissue [ 33 , 34 , 35 ]. A range between 0.3 μg/mL and 7 μg/mL gentamicin in skeletal muscle and tissue was reported in the literature after a 3 mg/kg/day dose [ 33 , 34 , 35 , 36 ]. To simulate a low gentamicin concentration in deep-seated infection, a gentamicin dose of 0.25 μg/mL or 0.5 μg/mL (0.5× MIC) was used in time-kill analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of ciprofloxacin in the subcutaneous tissue of this group of patients is related to the concentration of ciprofloxacin in plasma, the number of medications that the patients are taking and also on the severity of PAD. In a similar study conducted by Zammit et al 34 using gentamicin as the anti-infective agent of interest, gentamicin tissue concentrations were found to mostly depend on gender and degree of PAD severity.…”
Section: Discussionmentioning
confidence: 58%
“…There have been similar studies documenting the determination of other anti-infective agents in the tissue of patients suffering from PAD. 33,34 However, the distribution of ciprofloxacin in patients suffering from diabetic foot ulcers with varying degrees of PAD is not known and is being investigated in this study.…”
mentioning
confidence: 99%